2016
DOI: 10.1128/jvi.03116-15
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Capsid-Interacting Host Factors in Multimodal Inhibition of HIV-1 by PF74

Abstract: The viral capsid of HIV-1 interacts with a number of host factors to orchestrate uncoating and regulate downstream events, such as reverse transcription, nuclear entry, and integration site targeting. PF-3450074 (PF74), an HIV-1 capsid-targeting low-molecular-weight antiviral compound, directly binds to the capsid (CA) protein at a site also utilized by host cell proteins CPSF6 and NUP153. Here, we found that the dose-response curve of PF74 is triphasic, consisting of a plateau and two inhibitory phases of dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
81
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(97 citation statements)
references
References 70 publications
(247 reference statements)
12
81
1
Order By: Relevance
“…Therefore, we tested whether the A77V mutation also altered the cofactor utilization for nuclear entry by using RNA interference. Transient gene knockdown by siRNA, which was successfully used in our previous study (52,56), was validated by qRT-PCR of total cellular RNA. In two independent experiments, expression of TNPO3 and NUP153 was downregulated on average by 4.8-fold and 9.5-fold, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we tested whether the A77V mutation also altered the cofactor utilization for nuclear entry by using RNA interference. Transient gene knockdown by siRNA, which was successfully used in our previous study (52,56), was validated by qRT-PCR of total cellular RNA. In two independent experiments, expression of TNPO3 and NUP153 was downregulated on average by 4.8-fold and 9.5-fold, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…NUP358 was stably depleted from HeLa cells by using a puromycin-encoding lentiviral vector (pLKO.1; Addgene), which encodes the identical short hairpin RNA (shRNA) as a similar lentiviral vector used in our previous work (52). HeLa cell subclones (F1-5F and F1-8C) generated by two rounds of single-cell cloning, which were used in this study, were shown to exhibit a decreased level of NUP358 by a Western blot assay (56). In addition, silencing of each gene was validated by using quantitative reverse transcription-PCR (qRT-PCR) as described previously (51).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PF74 can destabilize the viral capsid, but its major antiviral effect occurs between reverse transcription and integration (19, 27, 49). The potency of PF74 antiviral activity depends on expression of host cell factors CypA, Nup153, and TNPO3 in target cells (23,28,49,50), and the PF74-binding pocket represents a binding site for host factor interactions, suggesting that the inhibitor's major effect is to alter virus-host cell interactions (19,24). While none of the currently reported CA-targeting compounds exhibits sufficient potency for clinical development, the variety of apparent antiviral mechanisms associated with such compounds suggests the intriguing possibility that the inhibitors act synergistically, and high potency may be achieved by creating bifunctional CAtargeting compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively high drug concentrations (~10 μM) block reverse transcription by probably accelerating capsid disassembly, whereas lower drug concentrations (~2 μM) block steps following reverse transcription, most likely nuclear entry [69, 72, 108, 140142]. In contrast to higher PF74 concentrations that block HIV-1 independent from host molecules, antiviral activity by low doses of PF74 depends on capsid interactions with CypA, NUP153, and CPSF6 [24, 112, 141], host factors implicated in HIV-1 PIC nuclear entry. Drug resistant mutations, which mapped within the binding pocket, altered the requirement for HIV-1 nuclear entry cofactors and conferred fitness costs prominently in primary cells [143, 144].…”
Section: Figurementioning
confidence: 99%